2014
DOI: 10.1111/iej.12268
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of intentional replantation with preoperative orthodontic extrusion: a retrospective study

Abstract: Intentional replantation was a viable treatment option for teeth with previously failed nonsurgical root canal treatment, regardless of a patient's age and gender, and tooth type and location. Preoperative orthodontic extrusion for 2-3 weeks reduced root resorption and tooth fracture and can be recommended to enhance the outcome of IR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
74
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(87 citation statements)
references
References 14 publications
(39 reference statements)
1
74
0
7
Order By: Relevance
“…Treatment variables associated with intentional replantation (apical diagnosis, preoperative antibiotic prophylaxis, prior NSRCT, type of root end filling material, antibiotic regimen, tooth splinting, and so on) have generally not been studied. However, Choi et al (36) retrospectively evaluated the effect of orthodontic extrusion before performing molar intentional replantation. Their sample size (N = 287) represented over one third of the teeth included in this systematic review (Table 1 and Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Treatment variables associated with intentional replantation (apical diagnosis, preoperative antibiotic prophylaxis, prior NSRCT, type of root end filling material, antibiotic regimen, tooth splinting, and so on) have generally not been studied. However, Choi et al (36) retrospectively evaluated the effect of orthodontic extrusion before performing molar intentional replantation. Their sample size (N = 287) represented over one third of the teeth included in this systematic review (Table 1 and Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, the data reported in Table 1 were considered to entail at least a 2-year mean follow-up; two studies had a mean follow-up of approximately 5 years, another had a median of approximately 6 years, some cases were followed for up to 22 years, and 1 study provided a 4-year Kaplan-Meier tooth survival curve. This Kaplan-Meier analysis indicated that most losses of IR teeth occurred within the first year, after which a steady state was reached (36). Only 2 of the intentional replant articles were published in the last dozen years; even these differed in clinical technique, hence limiting the definition of the nature of contemporary intentional replant practice, analysis, and interpretation.…”
Section: Description Of the Reported Literaturementioning
confidence: 98%
See 1 more Smart Citation
“…Lately, Choi et al suggested that using physics forceps could be considered as a reliable extraction instrument for a successful intentional replantation [14,15].…”
Section: Atraumatic Surgical Techniquementioning
confidence: 99%
“…As a matter of fact, 2 to 3 weeks before extraction, orthodontic extrusion can increase both tooth mobility and periodontal ligament volume permitting an easier extraction without a risk of tooth fracture [15].…”
Section: Atraumatic Surgical Techniquementioning
confidence: 99%